Association between daily use of social media and behavioral lifestyles in the Saudi community: a cross-sectional study - BinDhim, Nasser F.; Althumiri, Nora A.; Al-Duraihem, Rashed Abdullah; Alasmary, Saeed; Alkhamaali, Zaied; Alhabeeb, Abdulhameed Abdullah (Frontiers in Public Health, 2023)
Objective This study aimed to investigate the association between nine social media platforms use and health-related behavior, including fruit and vegetable intake, physical activity, tobacco use, and risk factors including depression and obesity. Methods A cross-sectional study was conducted using secondary data from the Sharik Health Indicators Surveillance System (SHISS). Participants 18 years and older were recruited via phone-interviews. The nine social media platform use [Twitter-(X), Facebook, Instagram, WhatsApp, LinkedIn, Snapchat, TikTok, Telegram, and YouTube] were assessed using self-reported use. Health-related variables include behavioral factors including diet, physical activity, and tobacco use including (cigarettes, waterpipes, and e-cigarettes), risk of depression and obesity. Logistic regression analysis was performed to explore the association between social media use and health-related variables. Results The study indicated that daily Snapchat users had a lower healthy diet (fruit and vegetable intake), whereas daily LinkedIn and WhatsApp users were positively associated with a healthier diet, relative to those with infrequent social media use. Furthermore, daily interaction with Instagram, TikTok, Telegram, and YouTube was significantly associated with increased depression risk. Conversely, Snapchat and WhatsApp usage was significantly linked to a decreased depression risk. Tobacco-smoking behaviors were associated with specific social media platforms: cigarette smoking was associated with Snapchat, TikTok, and YouTube; e-cigarette with Facebook, LinkedIn, Snapchat, and TikTok; and waterpipe smoking with Facebook and TikTok. Interestingly, some platforms, such as Instagram, were associated with reduced cigarette smoking. The relationship between social media activity and health-related outcomes remained significant after adjusting for age and gender. Conclusion This study highlights the potential negative impact of particular daily social media use on health-related variables, including dietary habits, tobacco use, and depression. Nevertheless, particular daily social media use of some platforms was associated with a potential positive impact on the health-related variables. Social media platforms are tools that can be used to achieve both a positive and negative effect. By knowing which demographic segments have a greater presence on one platform, we are creating opportunities to understand the social phenomena and at the same time use it to reach those segments and communicate with them, because each social media platform has its unique way and framework of user communication.